Identification of the optimal medical and surgical management for patients with perianal fistulising Crohn's disease. (13th September 2022) - Laland, Mathilde; François, Marie; D'Amico, Ferdinando; Zallot, Camille; Brochard, Charlène; Dewitte, Marie; Siproudhis, Laurent; Peyrin‐Biroulet, Laurent; Bouguen, Guillaume
Abstract: Aim: The aim of our study was to assess the best medical and surgical approaches for perianal Crohn's disease (PCD) in order to identify an optimal combined medical and surgical treatment. Methods: Medical records of all patients with PCD treated with TNFα antagonists in two referral centres between 1998 and 2018 were reviewed. Predictors of long‐term outcomes were identified using a Cox proportional hazard model. Results: A total of 200 patients were included. Fifty‐three patients (26.5%) were treated with adalimumab and 147 (73.5%) with infliximab. A combination of TNFα antagonist with an immunosuppressant and the presence of proctitis were independently associated with fistula closure. Seton was placed in 127 patients (63.5%) before starting biological therapy. Eighty patients (40%) underwent additional perineal surgery. Prior PCD surgery, seton positioning, additional perineal surgery, and additional surgery within 52 weeks of anti‐TNFα treatment were associated with an increased rate of fistula closure. Finally, medical combination therapy (anti‐TNFα plus immunosuppressant) along with seton placement and additional surgery within 1 year was the best management for PCD patients ( p  = 0.02). Conclusion: Combined medical and surgical management is required for the treatment of PCD patients. Medical combination therapy associated with seton placement and additional surgery within 1 year is the best management for PCD patients.